Prediction of operability of the plate rolling rolls based on the mixed fracture mechanism - Belodedenko, Sergey; Grechany, Alexey; Yatsuba, Andrey (Eastern-European Journal of Enterprise Technologies, 2018)
Influence of fracture of the mixed nature on the life of rolls of plate-rolling mills was considered. This is important because the time of trouble-free operation of plate-rolling rolls significantly affects the cost of the final product. However, there are objective difficulties connected with definition of the optimal model of prediction calculation of the final roll life because there is an insufficient definiteness of influence of the mixed fracture mechanism on the roll life. Conventionally, when predicting roll durability, a posteriori models of the roll service life obtained by the methods of mathematical statistics are used. However, the use of such models causes some complexity since preliminary processing of large volumes of statistical information is required. In the framework of the study described in the article, solution to this problem was proposed by determining influence of the mechanism of a mixed fracture on the roll life. This influence indicates the possibility of using the method of survivability curves for estimating the roll durability. Thus, an applied aspect of using the obtained scientific result is the possibility of improving the conventional method for calculating the roll service life. This, in turn, makes it possible to optimize previously obtained technological solutions for constructing a diagnostic algorithm of estimating the technical state of the plate-rolling rolls and predicting their residual life.